In vitro Characterization and Release Studies of Combined Nonionic Surfactant-Based Vesicles for the Prolonged Delivery of an Immunosuppressant Model Drug - Rasul, Akhtar (Int J Nanomedicine, 2020)
BACKGROUND: Cyclosporine A (CsA) is an exceptional immunosuppressant used for the treatment of immune disorders. Niosomal vesicles are promising drug carriers that are formed by self-association of nonionic surfactants and cholesterol in an aqueous phase. The objective of the study was to formulate combined nonionic surfactant based vesicles and to evaluate their in vitro characterization, release studies and in vivo studies. MATERIALS AND METHODS: Five niosomal formulations (F(7) to F(11)) were prepared using the thin film hydration method. The molar ratio of cholesterol and non-ionic surfactant taken was 1:1. In formulation F(10), the combination of surfactants Span 20 and Brij 35 was used. The niosomes were characterized by zeta sizer and SEM for particle size analysis, in vitro drug release and stability studies. The pharmacokinetic studies were conducted on healthy albino rabbits. RESULTS: The size of niosome was found in the range of 427.1 nm to 972.3 nm. SEM image of optimized formulations F(10) exhibit the spherical nature of niosomal vesicles. DSC thermograms of niosomal formulations exhibited a broadened endothermic peak. The stability study exhibited that all formulations are stable and negligible change of vesicle size and entrapment was observed with time. The percentage drug release was significantly higher as compared to CsA plain dispersion for all niosomal formulations at pH 1.2 and 7.4. The release kinetic behavior showed that all preparations were best described by zero order and can release active ingredient in a sustained manner. The pharmacokinetic data showed the test formulation (F10) possessed greater bioavailability as compared to the reference formulation (CsA aqueous dispersion). CONCLUSION: The formulation F(10) demonstrated a comparatively more delayed rate of release with enhanced dissolution as compared to a single surfactant scheme. The F(10) formulation can be a remarkable nanotechnology for prolonged delivery of CsA orally with improved dissolution profile and bioavailability.